Kinetics of aerobic and anaerobic biomineralization of atrazine in surface and subsurface agricultural soils in Ohio - Tuovinen, Olli H.; Deshmukh, Vaidehi; Ozkaya, Bestamin; Radosevich, Mark (TAYLOR & FRANCIS INC, 2015)
The purpose of this study was to assess atrazine mineralization in surface and subsurface samples retrieved from vertical cores of agricultural soils from two farm sites in Ohio. The Defiance site (NW-Ohio) was on soybean-corn rotation and Piketon (S-Ohio) was on continuous corn cultivation. Both sites had a history of atrazine application for at least a couple of decades. The clay fraction increased at the Defiance site and the organic matter and total N content decreased with depth at both sites. Mineralization of atrazine was assessed by measurement of (CO2)-C-14 during incubation of soil samples with [U-ring-C-14]-atrazine. Abiotic mineralization was negligible in all soil samples. Aerobic mineralization rate constants declined and the corresponding half-lives increased with depth at the Defiance site. Anaerobic mineralization (supplemented with nitrate) was mostly below the detection at the Defiance site. In Piketon samples, the kinetic parameters of aerobic and anaerobic biomineralization of atrazine displayed considerable scatter among replicate cores and duplicate biometers. In general, this study concludes that data especially for anaerobic biomineralization of atrazine can be more variable as compared to aerobic conditions and cannot be extrapolated from one agricultural site to another.
Keywords: Atrazine biodegradation; soil microbes; pesticide biodegradation; microbes in subsurface; biodegradation kinetics; BIODEGRADATION RATE; DEGRADATION; MINERALIZATION; WATER; DESORPTION; AQUIFER; ENVIRONMENT; ADSORPTION; MANAGEMENT; SEDIMENTS; Environmental Sciences & Ecology; Public, Environmental & Occupational Health